2004
DOI: 10.1016/j.jpainsymman.2003.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Pittsburgh sleep quality index in cancer patients

Abstract: This report summarizes findings related to the psychometric properties (internal consistency and construct validity) of the Pittsburgh Sleep Quality Index (PSQI) and discusses issues related to its use based on data from two clinical studies with diverse samples of cancer patients. Subjects completed a questionnaire that included the PSQI, the Schwartz Cancer Fatigue Scale, and specific demographic, disease, and treatment variables. There were complete data on 170 (of 214) cases in Study 1 and 249 (of 259) cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
298
4
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(333 citation statements)
references
References 19 publications
22
298
4
9
Order By: Relevance
“…36,37 Our review of the published literature revealed a wide range of reported Cronbach α for the PSQI, with a low of 0.43 (among Japanese healthy participants) to a high of 0.85 (among German patients with insomnia). [8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…36,37 Our review of the published literature revealed a wide range of reported Cronbach α for the PSQI, with a low of 0.43 (among Japanese healthy participants) to a high of 0.85 (among German patients with insomnia). [8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI.…”
Section: Discussionsupporting
confidence: 80%
“…[8][9][10][11][12][13][14][15][16][17][18] Though increasingly being used among pregnant women, 1,7,19 the psychometric properties of the PSQI has not been adequately assessed in this population. We are aware of only two published studies have evaluated the psychometric properties of the PSQI among pregnant women.…”
mentioning
confidence: 99%
“…The PSQI has good internal consistency (Cronbach's alpha=0.83) [6]. It has been validated in different populations such as patients with depression, in the bereaved, elderly, and patients with anxiety disorders, chronic pain and cancers [7][8][9].…”
Section: Excessive Daytime Sleepiness Resulting From Poor Sleep Ismentioning
confidence: 99%
“…Em dois estudos que abordam avaliação do sono em pacientes com câncer em quimioterapia, um com pacientes com câncer de pulmão 11 e outro com variados tipos 12 , obtiveram valores que indicam sono de má qualidade, sendo 6,8 naquele e 8,1 neste.…”
Section: Discussionunclassified